THE RELATIONSHIP BETWEEN FAMILY KNOWLEDGE AND THE CLIENT SOCIALIZATION ABILITY IN THE CITIZEN OF NANGKAAN SUB DISTRIC BONDOWOSO EAST JAVA - Yani, Achir; Hamid, Hamid; Mustikasari, Mustikasari (Jurnal Keperawatan, 2011)
Mental disorder, especially a psychotic (schizophrenia) is chronic condition that the clients have deterioration on their daily activity and social relationship (social isolation). The clients try to keep away from other interaction. This research aim was to identify the relationship between family knowledge and the client socialization ability. The design was a descriptive correlation with cross sectional. The samples were 78 families determined by total sampling. The inclusion criteria were thecitizen of Nangkaan sub distric, and accord as a respondent, having mental health disorders family member with social isolation, age between 18-60 years, and educational background at least Elementary School. The result shown that a significant relationship between family knowledge with the client socialization ability (value p < 0,05). Based on the result, it is recommended that the community nurse knowledge about social isolation client and family psycho education should beimproved.